[P137] Joint estimation of radiation-induced late toxicity and cancer recurrence risks for bilateral breast cancer after photon versus spot-scanning proton therapy. (August 2018) - Stick, Line Bjerregaard; Yu, Jen; Lundgaard, Anni Young; Vogelius, Ivan
Abstract : Purpose: Joint estimation of risks of radiation-induced secondary lung cancer (SLC) and ischemic heart disease (IHD) modeled with consideration of patient-level risk factors and risk of cancer recurrence caused by compromising target coverage. Methods: Five patients with bilateral breast cancer were treated with postoperative radiotherapy in 2013–2016: two patients received chest wall and comprehensive nodal irradiation (2 Gy x 25), two patients received whole breast irradiation (2.67 Gy x 15) and one patient received whole breast and left-sided lymph node irradiation (2 Gy x 25). Two patients were treated with 3D-CRT, three patients with VMAT. All patients were re-planned with intensity modulated spot-scanning proton therapy. One or three fields were used (anterior, left anterior oblique and right anterior oblique) with multi-field optimization. Models estimating risks of SLC and IHD were developed from published dose-response data and a model for risk of recurrence was derived based on hazard ratios from published randomized trials. Results: The average mean heart dose was 7.6 (range, 1.5–12.7) Gy for the photon plans while mean heart dose was below 0.4 Gy (RBE) for proton plans in all patients using protons (RBE, relative biological effectiveness, assuming RBE = 1.1). The average values of the mean lung dose and V20Gy were 12.2 (range, 5.2–16.3) Gy and 20.7% (range, 10.1%-27.4%) for photon plans, and 5.0 (range, 0.8–9.2) Gy (RBE) and 9.6% (range, 0.8%-19.1%) for proton plans. Median excess absolute risk (EAR) of SLC by age 80 for non-smokers/smokers was 2.6% (range, 0.6%-2.8%)/5.3% (range, 1.1%-5.7%) with photon therapy and 1.2% (range, 0.1%-1.6%)/2.4% (range, 0.2%-3.2%) with proton therapy. For the photon plans median EAR of IHD by age 80 was 2.8% (range, 0.2%-3.2%)/4.5% (range, 0.5%-5.6%) without/with cardiac risk factors whereas risks were below 0.2% for both scenarios using protons. Median EAR of recurrence or death by ten years was 0.9% (range, 0.1%-1.9%) with photons and 0.1% (range, 0.1%-0.3%) with protons. Conclusions: Proton therapy did reduce the predicted risk of SLC and IHD by up to 3.3% and 5.5%, respectively, and the risk of recurrence by up to 1.6% in individual patients.